A New Product Analysis and Decision Model - Urban, Glen L. (Management Science, 1968)
The decision to add, or to reject, or to investigate more fully a new product proposal is one of the most important problems faced by businessmen. The factors surrounding the decision can be mathematically considered by four sub-models in the areas of demand, cost, profit, and uncertainty. The demand model is structured to consider life cycle, industry, competitive and product interdependency effects, and will admit non-linear and discontinuous functions. A cost minimization model is joined to the demand model to formulate a constrained profit maximization problem. The optimization is accomplished by the use of dynamic programming. The final decision is based on the businessman's criterion in combining uncertainty and the rate of return on investment. A practical application of the model is presented to demonstrate the usefulness and problems of a quantitative approach to new product decisions.